2004
DOI: 10.1093/ajcn/79.5.820
|View full text |Cite
|
Sign up to set email alerts
|

Hypovitaminosis D is associated with insulin resistance and β cell dysfunction

Abstract: The data show a positive correlation of 25(OH)D concentration with insulin sensitivity and a negative effect of hypovitaminosis D on beta cell function. Subjects with hypovitaminosis D are at higher risk of insulin resistance and the metabolic syndrome. Further studies are required to explore the underlying mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

62
1,141
18
52

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,532 publications
(1,273 citation statements)
references
References 29 publications
62
1,141
18
52
Order By: Relevance
“…The CV for the total analytic precision of this assay was ≤ 9·9 % for 25(OH)D 3 and ≤ 5·9 % for iPTH (20,21) . The lower detection limit of this assay was 10·0 nmol/l for 25(OH)D 3 and 0·127 pmol/l for iPTH. Concentrations of 25(OH)D 3 <25 nmol/l were defined as vitamin D deficiency (22) .…”
Section: Laboratory Measurementsmentioning
confidence: 88%
See 1 more Smart Citation
“…The CV for the total analytic precision of this assay was ≤ 9·9 % for 25(OH)D 3 and ≤ 5·9 % for iPTH (20,21) . The lower detection limit of this assay was 10·0 nmol/l for 25(OH)D 3 and 0·127 pmol/l for iPTH. Concentrations of 25(OH)D 3 <25 nmol/l were defined as vitamin D deficiency (22) .…”
Section: Laboratory Measurementsmentioning
confidence: 88%
“…The objective of our study was to analyse whether vitamin D status, as measured by serum 25-hydroxycholecalciferol (25-hydroxyvitamin D 3 ; 25(OH)D 3 ) levels, and the levels of intact PTH (iPTH) are related to serum lipids and lipid ratios in non-institutionalised elderly people. Thereby, we took into account that these associations may depend on sex, age, body composition or lifestyle.…”
mentioning
confidence: 99%
“…Several large epidemiological studies have found 25(OH) D concentrations to be associated with improved insulin resistance and sensitivity (120)(121)(122) , but RCT have found mixed results; some have found a significant beneficial effect of supplementation (78,116,123) , while others have shown no effect (76,124) . An RCT in 100 apparently healthy, but centrally obese men observed an improvement in postprandial insulin sensitivity measured by the oral glucose insulin sensitivity index after supplementation with 3000 μg D 3 once a fortnight for 6 weeks: mean difference in change in oral glucose insulin sensitivity between placebo and the D 3 group was 41·1 (SE 15·5), P = 0·01 (78) .…”
Section: Insulin Sensitivity and Secretionmentioning
confidence: 99%
“…Pittas et al summarized the role of vitamin D on glucose metabolism [17,18]. Cross sectional and case control studies suggest an inverse association between vitamin D status, glucose intolerance and type 2 diabetes [19,20].This could be due the distribution of VDR on pancreatic beta cells, adipose tissue and skeletal muscle.…”
Section: Introductionmentioning
confidence: 99%